2014
DOI: 10.1002/ejoc.201402603
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Synthesis of (2R,3R)‐ and (2R,3S)‐3‐Hydroxypipecolic Acids, and Total Synthesis of (–)‐Deoxoprosopinine and (+)‐2‐epi‐Deoxoprosopinine from D‐Glycals

Abstract: Short and efficient formal syntheses of (2R,3R)‐ and (2R,3S)‐3‐hydroxypipecolic acids, and total syntheses of (–)‐deoxoprosopinine and (+)‐2‐epi‐deoxoprosopinine have been achieved starting from D‐glycals. The key steps involved in these syntheses were Ferrier rearrangement, azide reduction, intramolecular cyclization, and Grignard reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…At the same time, the pyrrolidine fragment was assembled from d -arabinose utilizing diastereoselective addition of Grignard reagent to nitrone 48 - 3 . Similarly, the heterocyclic cores of several relatively simple piperidine and pyrrolidine natural products, including fagomine derivatives, deoxoprosopine, and swainsonine, were assembled by the reaction between 1,4- or 1,5-disulfonates and primary amines. During the synthesis of the anticancer agent piperazimycin A, Ma and co-workers demonstrated that the nucleophilic substitution of sulfonate with hydrazine as a source of nitrogen can also be useful for the installation of the chiral center of the α-substituted hexahydropyridazine ring …”
Section: Stereoselective Formation Of C–n Bonds By Nucleophilic Subst...mentioning
confidence: 99%
“…At the same time, the pyrrolidine fragment was assembled from d -arabinose utilizing diastereoselective addition of Grignard reagent to nitrone 48 - 3 . Similarly, the heterocyclic cores of several relatively simple piperidine and pyrrolidine natural products, including fagomine derivatives, deoxoprosopine, and swainsonine, were assembled by the reaction between 1,4- or 1,5-disulfonates and primary amines. During the synthesis of the anticancer agent piperazimycin A, Ma and co-workers demonstrated that the nucleophilic substitution of sulfonate with hydrazine as a source of nitrogen can also be useful for the installation of the chiral center of the α-substituted hexahydropyridazine ring …”
Section: Stereoselective Formation Of C–n Bonds By Nucleophilic Subst...mentioning
confidence: 99%
“…Having diols 7a-d in hand, these were converted into their corresponding dimesylates under conventional conditions (MsCl, Et 3 N, CH 2 Cl 2 , 0 °C, 2 h) to furnish the desired precursors 5a (91%), 5b (90%), 5c (92%), 5d (89%, Scheme 6). The dimesylates 5a-d were subjected to bisnucleophilic substitution 13 with benzlamine independently to afford the benzyl-protected piperidines 27a (92%), 27b (95%), 27c (94%), and 27d (91%).…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…These compounds are β-turn inducers in the synthesis of peptides [4] and good enzyme inhibitors by themselves [5] as are several of their derivatives, such as deoxy-galactono-jirimicin derivatives [6,7,8]. Indeed, stereoselective synthesis of hydroxy-amino acids is a field that has been growing during the last decades because of the potential biological activity of some representatives of this class of compounds, mainly as enzyme inhibitors [5,9,10,11,12]. Particularly, conformationally constrained hydroxy-amino acids such as the hydroxylated pipecolic acids are very interesting target molecules [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, stereoselective synthesis of hydroxy-amino acids is a field that has been growing during the last decades because of the potential biological activity of some representatives of this class of compounds, mainly as enzyme inhibitors [5,9,10,11,12]. Particularly, conformationally constrained hydroxy-amino acids such as the hydroxylated pipecolic acids are very interesting target molecules [12,13]. For instance, the compound (2 S ,4 R )-4-hydroxy-pipecolic acid is a natural product that has been isolated from Calliandra pittieri and Stophantus scandeus [14], and the cis -5-hydroxy-substituted pipecolic acid skeleton is frequently found in alkaloids from microorganisms and also in plants (febrifugine, pseudoconhidrine) [15,16].…”
Section: Introductionmentioning
confidence: 99%